Diffusive loss of argon in response to melt vein formation in polygenetic impact melt breccias. Issue 8 (1st August 2017) - Mercer, Cameron M.; Hodges, Kip V.
Abstract: Many planetary surfaces in the solar system have experienced prolonged bombardment. With each impact, new rocks can be assembled that incorporate freshly generated impact melts with fragments of older rocks. Some breccias can become polygenetic, containing multiple generations of impact melt products, and can potentially provide important insights into the extensive bombardment history of a region. However, the amount of chronological information that can be extracted from such samples depends on how well the mineral isotopic systems of geochronometers can preserve the ages of individual melt generations without being disturbed by younger events. We model the thermal evolution of impact melt veins and the resulting loss of Ar from K‐bearing phases common in impact melt breccias to assess the potential for preserving the 40 Ar/ 39 Ar ages of individual melt generations. Our model results demonstrate that millimeter‐scale, clast‐free melt veins cause significant heating of adjacent host rock minerals and can cause detectable Ar loss in contact zones that are generally thinner than, and at most about the same thickness as, the vein width. The incorporation of cold clasts in melt veins reduces the magnitudes of heating and Ar loss in the host rocks, and Ar loss can be virtually undetectable for sufficiently clast‐rich veins. Quantitative evidence of the timing of impacts, as measured with the 40 Ar/ 39 Ar method, can be preserved in polygenetic impact melt breccias, particularly for those containing millimeter‐scale bodies of clast‐bearing melt products. Plain Language Summary: Many planets, moons, and asteroids in the solar system have experienced extensive impact bombardment throughout their histories. With each impact, new rocks can be assembled that incorporate fragments of older rocks and freshly melted rock produced by the energy of impact. The molten portions eventually cool, and the combination of older and younger materials, which we call an impact melt breccia (IMB), becomes a time capsule with a record of the impacts that the IMB has endured. Radioactive elements trapped in the minerals of the breccia act as clocks called geochronometers, which we can potentially use to unravel the timing of the impacts. We model how much these geochronometers are heated in older rock fragments when new impact melts form and cool and assess how much the geochronometers of older materials can be disturbed. We found that geochronometers are not heavily affected in breccias that incorporate thin, millimeter‐scale melt bodies, especially if the new melt bodies also contain older rock fragments. Therefore, IMBs that contain multiple generations of rocks and now‐solidified impact melts can accurately record the timing of each of the impacts that affected it. Key Points: 40 Ar/ 39 Ar geochronology can provide robust ages for different melt formation events in polygenetic impact melt breccias Clast‐free melt veins can cause heating and Ar loss from contact zones up to the width of the vein Clast‐bearing impact melt veins significantly reduce heating and Ar loss from the contact zones